The professional identity of Jewish thought teachers in Israel’s state religious education system - Levin, Ariel (British Journal of religious education, 2026)
This study examines the professional identity of teachers of Jewish thought within Israel’s state-religious education system. Despite the pivotal role of Jewish thought in shaping students’ religious consciousness, no comprehensive study has yet addressed the professional identity of educators in this field. Utilising semi-structured, in-depth interviews with 15 teachers, the study identifies four central components shaping their professional identity: their perception of their role as shapers of consciousness and belief, the tension between exercising leadership and maintaining flexibility in guiding educational processes, their commitment to continuous professional development, and the pedagogical challenges of rendering traditional content, utilising the language of ancient texts accessible to 21st-century students. The significance of this study lies in its contribution to theoretical knowledge regarding the professional identity of educators in religious philosophy, its elucidation of the challenges involved in teaching Jewish thought in the contemporary era, and its implications for teacher training and professional development programmes. These findings offer valuable insights into the complexity of the role of educators engaged in teaching philosophical-religious content within modern educational contexts.